Biogas measurement techniques and the associated errors - Parajuli, Prakash (2011)
There are several techniques for the measurement of laboratory scale biogas production. This thesis describes the study and evaluation of the most significant and commonly used biogas measurement techniques and analyzes the source of errors associated with the measurement of biogas production. Firstly, inaccuracy mainly due to biogas carbon dioxide (CO₂) dilution in displaceable liquids and losses to atmosphere of dissolved CO₂ was evaluated by testing solubility of CO₂ in different barrier solutions. Saturated acidified brine solution showed lower CO₂ solubility among the tested solutions. An accurate, simple, automated and easy to calibrate laboratory scale liquid displacement gas measuring device was built and tested. Headspace gas chromatography (HS-GC) analysis and errors that could arise due to solubility, concentration and temperature influence were also investigated. Experimental analysis using dry and saturated synthetic bio-gas samples were carried at different temperatures. Gas chromatography results showed significant changes in methane (CH4) and CO₂ concentration when incubated at 5, 35, 55 & 70 °C and compared with standard prepared at room temperature (23 °C). Errors at thermphilic temperatures were much higher than at 35 or 5 °C. One of the possible and easy means of avoiding errors was found by maintaining the same temperature for both standard and samples during the entire GC experimental analysis. This was performed by cooling the assays to room temperature for a short period of measurement time. This short fluctuation of temperature and its effect on the entire anaerobic process and microbiological activity was also examined. Errors that could arise during the gas measurement and analysis were pointed out and the possible means of corrections were discussed.